Menejemen Perawatan Diri Untuk Meningkatkan Pengetahuan Keluarga Dan Pasien Gagal Jantung Di Desa Mendatte - Hasna, Hasna; Rante, Anshar; Rasyid, Djusmadi; Warda, Warda; Sariati, Marwa (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Heart failure is the most common cardiovascular disease and is associated with uncontrolled risk factors. Self-care management is the ability of heart failure patients to manage themselves and their disease. Based on research data from the service center, there are 30 heart failure patients and 30 heart failure patients in the family. The purpose of the service is to expand the knowledge and skills of families and heart failure patients in self-care. The counseling was held in the health center building which was attended by 30 patients with heart disease. Newspaper media was used as a tool in counseling activities, which was delivered by the speaker orally within 45 minutes, and continued with evaluation and renewal of evidence. The results showed that 90% of respondents understood the material provided. This was reflected in the answers to questions and the willingness of families and patients to exercise again after the simulation during the evaluation. Self-care management can be improved through training and simulation